Identifikasi Kandungan Logam Berat Kadmium (Cd) Pada Sapi Potong Yang Dipelihara Di Tempat Pembuangan Akhir (Tpa) Kecamatan Alak, Kota Kupang - Timothy Kondanamu Nangkiawa; Annytha Ina Rohi Detha; Nemay Anggadewi Ndaong (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
One of m ajor obstacle for cattle breeding enterprise in an urban area called Kupang city is the limited availability of grazing land . Attempting to overcome this , farmers in Kupang to utilize Alak final disposal (landfill) WITHOUT graz land of Alak. The purpose of this research was to identify the content of heavy metal cadmium (Cd) in cattle reared on waste/final disposal in Alak, Kupang . 12 blood samples were taken on the basis of various criteria , namely from the age group of 0 to 1.5 years of age; age group of 1.5 to 3 years and a group of more than 3 years. 3 ml blood samples were determined/ were measured by atomic absorption spectrophotometry in the Quality Testing Center and Animal Product Certification in Bogor. Results showed that the highest number was 0 .0297 ug/ml in the age group of 0 to 1.5 years) and the lowest was 0.0170 ug/ml in the age group over 3 years. Results showed that the highest number was 0.0297 ug/ml in the age group of 0 to 1.5 years) and the lowest was 0.0170 ug/ml in the age group ove r 3 years. In conclusion, 100% of heavy metal Cadmium was accumulated in beef cattle raised on Alak landfills and it might harmful to be consumed by people who live in kupang.